Anatomopathological and Immunohistochemical Apects of Distemper Virus in Crab-Eating-Foxes and Pampa-Foxes - Slaviero, Mônica; Ehlers, Luiza Presser; De Lorenzo, Cíntia; Zafalon-Silva, Bruna; Driemeier, David; Pavarini, Saulo Pettinati; Alievi, Marcelo Meller; Sonne, Luciana (Acta Scientiae Veterinariae, 2019)
Background: Distemper is a contagious disease with worldwide distribution, which is caused by a single-stranded RNA virus of the genus Morbillivirus. The Crab-eating fox (Cerdocyon thous) and the Pampas fox (Lycalopex gymnocercus), wild canids commonly found in the state of Rio Grande do Sul, are highly susceptible to the disease. Distemper virus infection often shows a multisystemic presentation. Central nervous system lesions are frequently reported, and may lead to death of wild canids. Distemper virus infection affecting these species has been cited by several studies; nonetheless, case descriptions involving the Crab-eating fox and the Pampas fox are infrequent. Therefore, the objective of the present study is to describe the anatomopathological and immunohistochemical aspects of distemper in the referred species, aiming to assist with the diagnosis of the disease. Materials, Methods & Results: A retrospective study was performed, and the necropsy reports of Crab-eating foxes and Pampas foxes admitted to SPV-UFRGS from 2010 to 2016 were reviewed. Necropsy reports were revised in order to obtain information related to the clinical history and anatomopathological findings, and cases compatible with distemper were selected. Data regarding the affected species, sex, approximate age, origin and clinical signs were compiled and analyzed. Selected histological sections of brain and cerebellum were submitted for immunohistochemistry (IHC) for monoclonal antibody canine distemper virus. In the studied period, 20 animals of the referred species were subjected to necropsy, of which four were diagnosed with distemper as a cause of death. Of the affected animals, two were female and two were male. Three were juvenile and one was an adult animal. Clinical signs reported included myoclonia, opisthotonos, forelimb paresis and nystagmus. No significant gross changes were noted. Histopathological findings were restricted to the central nervous system, especially in the cerebellum, and the main lesion was demyelination, as well as gemistocytic astrocytes, malacia with Gitter cells, gliosis and perivascular cuffing. Inclusion bodies were observed in only one case. Diffuse and marked viral antigen positive immunostaining was detected, mainly in the cytoplasm of astrocytes, predominantly in the cerebellum. Discussion: The diagnosis of distemper affecting the Crab-eating fox and Pampas fox was based on the clinical and histopathological findings, along with viral antigen identification through immunohistochemistry. Clinical signs were restricted to the central nervous system and were associated with the affected area. Significant gross changes in the central nervous system were not observed, similarly to what has been described by other authors. The main histological lesion was demyelination in the cerebellum, which is in agreement with previous reports in wild canids. Similarly to the findings reported in dogs and mustelids, positive immunostaining was observed mainly in the cytoplasm of astrocytes in the cerebellum; however, in our cases diffuse marked staining was noted. Although some authors have reported that viral antigens disappear in demyelinating lesions, due to the inflammation associated with the host immune response, the opposite was observed in the present study, suggesting viral persistency linked to a weak immune response in these species. The clinical and pathological changes observed were compatible with the neurologic phase of distemper; therefore, it is important to include this agent among the differential diagnosis in the referred wild canids, mainly in animals presenting neurological signs. Immunohistochemichal evaluation was important to the establishment of postmortem diagnosis of distemper, since characteristic viral inclusion bodies were rarely observed through histopathology.